Overcoming EGFR(T790M) and EGFR(C797S) resistance with mutant-selective allosteric inhibitors - Jia, Yong; Yun, Cai-Hong; Park, Eunyoung; Ercan, Dalia; Manuia, Mari; Juarez, Jose; Xu, Chunxiao; Rhee, Kevin; Chen, Ting; Zhang, Haikuo; Palakurthi, Sangeetha; Jang, Jaebong; et al. (Nature (London), 2016)
An allosteric inhibitor, EAI045, is reported that is selective for certain drug-resistant EGFR mutants, but spares the wild-type receptor; combination therapy of EAI045 with EGFR-dimerization-blocking antibodies is effective in mouse models of lung cancer driven by mutant versions of EGFR that are resistant to all previously developed inhibitors. Novel EGFR-directed therapeutics Currently available small-molecule inhibitors targeting epidermal growth factor receptor (EGFR) and other receptor tyrosine kinases bind the ATP site of the kinase, and therefore typically inhibit a number of 'off-target' kinases owing to the high conservation of this site. In addition, the common binding site of these drugs leads to shared susceptibility to resistance-conferring mutations in EGFR. Here, Michael Eck and colleagues describe an allosteric inhibitor, EAI045, that is selective for certain drug-resistant EGFR mutants but spares the wild-type receptor. Although EAI045 is not effective in blocking EGFR-driven cell proliferation as a single agent, it has synergistic inhibitory activity when combined with an antibody that blocks EGFR dimerization. This combination therapy is effective in mouse models of lung cancer driven by mutant versions of EGFR that are resistant to all previously developed inhibitors. The epidermal growth factor receptor (EGFR)-directed tyrosine kinase inhibitors (TKIs) gefitinib, erlotinib and afatinib are approved treatments for non-small cell lung cancers harbouring activating mutations in the EGFR kinase 1 , 2 , but resistance arises rapidly, most frequently owing to the secondary T790M mutation within the ATP site of the receptor 3 , 4 . Recently developed mutant-selective irreversible inhibitors are highly active against the T790M mutant 5 , 6 , but their efficacy can be compromised by acquired mutation of C797, the cysteine residue with which they form a key covalent bond 7 . All current EGFR TKIs target the ATP-site of the kinase, highlighting the need for therapeutic agents with alternative mechanisms of action. Here we describe the rational discovery of EAI045, an allosteric inhibitor that targets selected drug-resistant EGFR mutants but spares the wild-type receptor. The crystal structure shows that the compound binds an allosteric site created by the displacement of the regulatory C-helix in an inactive conformation of the kinase. The compound inhibits L858R/T790M-mutant EGFR with low-nanomolar potency in biochemical assays. However, as a single agent it is not effective in blocking EGFR-driven proliferation in cells owing to differential potency on the two subunits of the dimeric receptor, which interact in an asymmetric manner in the active state 8 . We observe marked synergy of EAI045 with cetuximab, an antibody therapeutic that blocks EGFR dimerization 9 , 10 , rendering the kinase uniformly susceptible to the allosteric agent. EAI045 in combination with cetuximab is effective in mouse models of lung cancer driven by EGFR(L858R/T790M) and by EGFR(L858R/T790M/C797S), a mutant that is resistant to all currently available EGFR TKIs. More generally, our findings illustrate the utility of purposefully targeting allosteric sites to obtain mutant-selective inhibitors.